Unfair Dismissal Law and Temporary Migrant Labour in Australia. (2018) - Howe, Joanna; Berg, Laurie; Farbenblum, Bassina
Increasing attention is being given to the exploitation of temporary migrant workers in Australia, in particular in relation to wage underpayments. But very little focus has been given to the ability of temporary migrant workers to access legal remedies under Australian employment law. This article examines whether temporary migrant workers are able to make and pursue a claim for unfair dismissal within the federal jurisdiction. As unfair dismissal law seeks to protect job security and provides an essential check on managerial prerogative, it is important that temporary migrant workers are able to access this legal avenue to protect them from arbitrary dismissal. We argue there are serious deficiencies in the application, coverage and content of federal unfair dismissal law in relation to temporary migrant workers in Australia.